2019
DOI: 10.1037/neu0000505
|View full text |Cite
|
Sign up to set email alerts
|

Multimethod assessment of everyday functioning and memory abilities in Parkinson’s disease.

Abstract: This study compared functional abilities in individuals with Parkinson's disease (PD) with normal cognition (PD-CN) and mild cognitive impairment (PD-MCI) using multiple assessment methods. Cognitive and physical correlates were also examined. Method: Participants were 42 nondemented individuals with PD (24 PD-CN, 18 PD-MCI) and 42 age-matched healthy controls. Functional abilities were assessed through direct observation and self-and informant-report questionnaires. Participants were administered an activity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…As cognitive performance was lower in PD-MCI patients with an ETAM total score below 27, we argue that the ETAM is a valuable performance-based test to identify cognitive-driven iADL impairment in a subgroup of PD-MCI patients we assume are at a higher risk for PDD development. Especially, as iADL dysfunction has been associated with decline in attention, memory, executive, and visuospatial function (Bronnick et al, 2006;Cahn et al, 1998;Fellows & Schmitter-Edgecombe, 2019;Higginson et al, 2013;Maeshima et al, 1997;Pirogovsky et al, 2012). These cognitive domains also showed high associations to the ETAM scores in our study.…”
Section: Etam Sensitivity For Iadl Impairment Associated With Pd-mcisupporting
confidence: 66%
See 1 more Smart Citation
“…As cognitive performance was lower in PD-MCI patients with an ETAM total score below 27, we argue that the ETAM is a valuable performance-based test to identify cognitive-driven iADL impairment in a subgroup of PD-MCI patients we assume are at a higher risk for PDD development. Especially, as iADL dysfunction has been associated with decline in attention, memory, executive, and visuospatial function (Bronnick et al, 2006;Cahn et al, 1998;Fellows & Schmitter-Edgecombe, 2019;Higginson et al, 2013;Maeshima et al, 1997;Pirogovsky et al, 2012). These cognitive domains also showed high associations to the ETAM scores in our study.…”
Section: Etam Sensitivity For Iadl Impairment Associated With Pd-mcisupporting
confidence: 66%
“…A range of performance-based tests already exist and some of them have been used in PD cohorts. However, they are either timeconsuming in either assessment and/or scoring [Direct Assessment of Functional Status (Brennan et al, 2016;Deck et al, 2019); Older Americans Resources and Services scale (Shulman et al, 2006); Naturalistic Action Test (Roll, Giovannetti, Libon, & Eppig, 2019); Financial capacity instrument (FCI) (Martin et al, 2013); Medication Management Ability Assessment (Pirogovsky et al, 2013); Multiple Object Test (MOT) (Beyle et al, 2018;Glonnegger et al, 2016)], need extraordinary materials [Six activities task (Fellows & Schmitter-Edgecombe, 2019)], are assessed in a domestic environment [Performance Assessment of Self-Care Skills, (Foster, 2014)], correlate with PD-related motor symptoms [University of California San Diego Performance-Based Skills Assessment, UPSA (Holden et al, 2018)], or motor influences on the performance-based test have not been examined in PD studies yet [Timed Instrumental Activities of Daily Living scale (Higginson, Lanni, Sigvardt, & Disbrow, 2013)]. In Alzheimer's disease research, a performance-based test for mild cognitive impairment (MCI) and early dementia was recently developed: the Erlangen Test of Activities of Daily Living in Persons with Mild Dementia and Mild Cognitive Impairment (ETAM).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the complexity of DBS neurosurgical treatment, only IADL self-report and cognitive, depressive, and clinical correlates were included in the current research. In comparison to other studies that concentrated either on IADL predictors or the quantification of the degree of IADL deficits in PD-NC in comparison to PD-MCI (Rosenthal et al, 2010;Pirogovsky et al, 2013;Foster, 2014;Fellows and Schmitter-Edgecombe, 2019;Becker et al, 2020;Cholerton et al, 2020;Foster and Doty, 2021;Schmitter-Edgecombe et al, 2021;Becker et al, 2022), or comparison and development of specific methods and sensitive IADL items for PD (Brennan et al, 2016a,b;Fellows and Schmitter-Edgecombe, 2019;Sulzer et al, 2020;Schmitter-Edgecombe et al, 2021), whereas our study focused selectively on the comparison of IADL in PD before and after STN-DBS with a PD-specific questionnaire (Brennan et al, 2016a,b). We based our estimate of the post-surgery IADL change on an explicit causal model allowing for easier model criticism and derivation of proper covariates to include in our model (Pearl, 2009;McElreath, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Both ADL impairments and severe cognitive impairment result in increased risk for nursing home placement and mortality (Hosking et al, 2021). Recent studies have shown that even patients with mild cognitive impairment (PD-MCI) display first signs of ADL dysfunction (Pirogovsky et al, 2014;Cheon et al, 2015;Fellows and Schmitter-Edgecombe, 2019), possibly indicating a group at risk for dementia (Beyle et al, 2018). As the diagnosis of ADL deficits requires these to be solely caused by cognitive deficits, an important step for accurate diagnoses is the measurement of ADL deficits in PD.…”
Section: Introductionmentioning
confidence: 99%